In Conversation with Filmmaker Ines Johnson-Spain (2022)
In October 2022, the Africa Mulitple Cluster of Excellence invited filmmaker Ines Johnson-Spain to show her film "Becoming Black" for a group of young students. The discussion that ensued was both interesting and enlightening with the students asking questions about the porcess of making a movie to societal questions about racism. Later that day, the filmmaker sat down with PhD student Marie Tsogo to discuss her movie and biography. In her autobiographical documentary "Becoming Black" Ines Johnson-Spain takes the audience on the route of discovery of her roots and paternal family after having grown up in the German Democratic Republic.